Multifunctional Pt(iv) prodrug candidates featuring the carboplatin core and deferoxamine. Issue 23 (25th May 2021) - Harringer, Sophia; Hejl, Michaela; Enyedy, Éva A.; Jakupec, Michael A.; Galanski, Mathea S.; Keppler, Bernhard K.; Dyson, Paul J.; Varbanov, Hristo P.
Abstract : Five new multifunctional Pt(iv ) prodrugs with a carboplatin core and one or two axial deferoxamine ligands were synthesized. The complexes express multiple effects, including cytotoxicity and high affinity towards ferric ions. Abstract : The synergistic combination of the anticancer drug carboplatin and the iron chelator deferoxamine (DFO) served as a foundation for the development of novel multifunctional prodrugs. Hence, five platinum(iv ) complexes, featuring the equatorial coordination sphere of carboplatin, and one or two DFO units incorporated at axial positions, were synthesized and characterized using ESI-HRMS, multinuclear ( 1 H, 13 C, 15 N, 195 Pt) NMR spectroscopy and elemental analysis. Analytical studies demonstrated that the chelating properties of the DFO moiety were not compromised after coupling to the platinum(iv ) core. The cytotoxic activity of the compounds was evaluated in monolayer (2D) and spheroid (3D) cancer cell models, derived from ovarian teratocarcinoma (CH1/PA-1), colon carcinoma (SW480) and non-small cell lung cancer (A549). The platinum(iv )–DFO prodrugs demonstrated moderate in vitro cytotoxicity (a consequence of their slow activation kinetics) but with less pronounced differences between intrinsically chemoresistant and chemosensitive cell lines as well as between 2D and 3D models than the clinically used platinum(ii ) drug carboplatin.